Quasinormal corrections to near-extremal black hole thermodynamics - Daniel Kapec; Y. T. Albert Law; Chiara Toldo (Journal of High Energy Physics)
Abstract Recent work on the quantum mechanics of near-extremal non-supersymmetric black holes has identified a characteristic T 3/2 scaling of the low temperature black hole partition function. This result has only been derived using the path integral in the near-horizon region and relies on many assumptions. We discuss how to derive the T 3/2 scaling for the near-extremal rotating BTZ black hole from a calculation in the full black hole background using the Denef-Hartnoll-Sachdev (DHS) formula, which expresses the 1-loop determinant of a thermal geometry in terms of a product over the quasinormal mode spectrum. We also derive the spectral measure for fields of any spin in Euclidean BTZ and use it to provide a new proof of the DHS formula and a new, direct derivation of the BTZ heat kernel. The computations suggest a path to proving the T 3/2 scaling for the asymptotically flat 4d Kerr black hole.